Combined effect of cigarette smoking and prediabetes on structural and functional changes of large arteries. (25th November 2020) - Ioakeimidis, N; Dima, I; Terentes-Printzios, D; Georgakopoulos, C; Angelis, A; Gourgouli, I; Solomou, E; Skoumas, I; Tousoulis, D; Vlachopoulos, C
Abstract: Purpose: Smoking is a major risk factor for cardiovascular disease and prediabetes is associated with excess risks for adverse cardiovascular outcomes and death. Aim of this study was to explore whether smoking and prediabetes exert a synergistic unfavourable effect on functional and structural parameters of large arteries. Methods: We measured carotid-femoral pulse wave velocity (cfPWV), augmentation index (AIx) and carotid intima media thickness (cIMT) in 407 individuals without known atherosclerotic disease (mean age: 52±8 years) categorized into four age-matched groups according to glucose metabolic and smoking status: Smokers with diabetes (n=68), Smokers with prediabetes (n=87), Non-smokers with prediabetes (n=98) and Non- smokers with normal fasting blood glucose (FBG) (n=154). Prediabetes was defined as impaired fasting glucose (100–125 mg/dL), impaired glucose tolerance (2-hour glucose level of 140–199 mg/dL during an oral glucose tolerance test), or glycosylated hemoglobin (HbA1c) level of 5.7% to 6.4%. High sensitivity C-reactive protein (hsCRP) was measured in all patients. Results: Systolic pressure, pulse pressure were increased and hsCRP levels were higher in smokers with diabetes compared to the three other groups (overall P<0.05, P<0.01 and P<0.05, respectively, ANOVA). The cumulative tobacco exposure (measured in pack-years) was similar between smokers with diabetes and smokers with prediabetes (45 pack-years). Figure 1 shows cfPWV, AIx and cIMT of the four groups. Interestingly, smokers with diabetes and smokers with prediabetes have similar mean cfPWV and cIMT and significantly higher values compared to non-smokers with prediabetes and non-smokers with normal FBG. The associations remained statistically significant even after adjusting for systolic pressure and hsCRP level. AIx was not different between the four study groups. Conclusion: The combination of prediabetes and smoking is associated with higher cfPWV and cIMT values compared to prediabetes alone. The smokers with impaired glucose regulation have functional and structural alterations of large arteries similar to that of smokers with established diabetes. Considering the risk for developing prediabetes in relation to smoking status and the number of cigarettes smoked daily and the independent predictive value of assessing vascular changes in large arteries, the present findings may have important clinical and prognostic implications. Funding Acknowledgement: Type of funding source: None